This Much Country : A Memoir - Pace, Kristin Knight (New York : Grand Central Publishing, 2020)
In 2009, after a crippling divorce that left her heartbroken and directionless, Kristin decided to accept an offer to live at a friends cabin outside of Denali National Park in Alaska for a few months. In exchange for housing, she would take care of her friends eight sled dogs. That winter, she learned that she was tougher than she ever knew. She learned how to survive in one of the most remote places on earth and she learned she was strong enough to be alone. She fell in love twice: first with running sled dogs, and then with Andy, a gentle man who had himself moved to Alaska to heal a broken heart. Kristin and Andy married and started a sled dog kennel. While this work was enormously satisfying, Kristin became determined to complete the Iditarod -- the 1,000-mile dogsled race from Anchorage, in south central Alaska, to Nome on the western Bering Sea coast. "This Much Country" is the story of renewal and transformation. Its about journeying across a wild and unpredictable landscape and finding inner peace, courage and a true home. Its about pushing boundaries and overcoming paralyzing fears.
Keywords: Sled dog racing -- Alaska; Women mushers -- Alaska; Biography; Mushers -- Alaska; Biography; Autobiography